Pulmonary Hypertension and Indicators of Right Ventricular Function - von Siebenthal, Célia; Aubert, John-David; Mitsakis, Periklis; Yerly, Patrick; Prior, John O.; Nicod, Laurent Pierre (Frontiers in Medicine, 2016)
Pulmonary hypertension (PH) is a rare disease, whose underlying mechanisms are not fully understood. It is characterized by pulmonary arterial vasoconstriction and vessels wall thickening, mainly intimal and medial layers. Several molecular pathways have been studied, but their respective roles remain unknown. Cardiac repercussions of PH are hypertrophy, dilation and progressive right ventricular dysfunction. Multiple echocardiographic parameters are being used, in order to assess anatomy and cardiac function, but there are no guidelines edited about their usefulness. Thus, it is now recommended to associate the best-known parameters, like atrial and ventricular diameters or tricuspid annular plan systolic excursion (TAPSE). Cardiac catheterization remains necessary to establish the diagnosis of PH and to assess pulmonary hemodynamic state. Concerning energetic metabolism, free fatty acids, normally used to provide energy for myocardial contraction, are replaced by glucose uptake. These abnormalities are illustrated by increased 18F-FDG uptake on PET/CT, which seems to be correlated with echocardiographic and hemodynamic parameters.